2017
DOI: 10.1002/jgt.22148
|View full text |Cite
|
Sign up to set email alerts
|

Graph operations and upper bounds on graph homomorphism counts

Abstract: We construct a family of countexamples to a conjecture of Galvin [5], which stated that for any n‐vertex, d‐regular graph G and any graph H (possibly with loops), homfalse(G,Hfalse)≤max{hom(Kd,d,H)n2d,hom(Kd+1,H)nd+1},where hom(G,H) is the number of homomorphisms from G to H. By exploiting properties of the graph tensor product and graph exponentiation, we also find new infinite families of H for which the bound stated above on hom(G,H) holds for all n‐vertex, d‐regular G. In particular, we show that if HWR is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…It was conjectured [32] that one of K d,d and K d+1 always maximizes hom(G, H) 1/v(G) for every H. However, Sernau [52] showed that this is false (a similar construction was independently found by Pat Devlin).…”
Section: 2mentioning
confidence: 98%
See 4 more Smart Citations
“…It was conjectured [32] that one of K d,d and K d+1 always maximizes hom(G, H) 1/v(G) for every H. However, Sernau [52] showed that this is false (a similar construction was independently found by Pat Devlin).…”
Section: 2mentioning
confidence: 98%
“…The following special case, proved in [10] (prior to [52]), provides some a nice family of examples.…”
Section: Graph Products and Powersmentioning
confidence: 99%
See 3 more Smart Citations